Protocol for a multicentre, prospective cohort study of clinical, proteomic and genomic patterns associated with osteoporosis to develop a multidimensional fracture assessment tool: the PoCOsteo Study - Noushin Fahimfar; Bagher Larijani; Afshin Ostovar; Iraj Nabipour; Patricia Khashayar; Hans Peter Dimai; Nahid Moradi; Safoora Gharibzadeh (BMJ Open)
Introduction The HORIZON 2020 project PoCOsteo aims (1) to develop a multidimensional fracture risk assessment tool which would take into account all factors known to be related to an individual’s fracture risk. The fracture risk model is intended to be developed in two different populations, namely a European and a Middle Eastern one; (2) to develop a medical device, which would measure and/or quantify proteomic as well as genomic factors as present in whole blood samples collected through finger prick; (3) to test the clinical applicability and the validity of prototypes of the to be developed point of care device at both clinical centres.Methods and analysis This article presents the protocol of this prospective cohort that will be carried out independently at two different centres (Division of Endocrinology and Diabetology at the Medical University of Graz (MUG) as a clinic-based cohort, and Endocrinology and Metabolism Research Institute (EMRI) at the Tehran University of Medical Sciences (TUMS) as a population-based cohort). The final aim is to develop a fracture risk assessment model, which would include clinical risk factors, biochemical markers of bone turnover, as well as specific genomic factors. The derivation cohorts will consist of individuals aged 50 years and above. The period of observation for each patient will be 12 months; an extension phase, which would last for another 2 years, is also planned.Ethics and dissemination These studies are conducted in accordance with the World Medical Association Declaration of Helsinki. The Iranian part was approved by the Research Ethics Committee of EMRI, TUMS. The Austrian part was approved by the Ethics Committee of the Medical University of Graz. Based on the gathered information, a multidimensional fracture assessment tool will be designed which will later be added to the PoCOsteo device.